"Estructuración del sistema para la comercialización de ropa casual en el sector sur de Quito". - Cañar Guamán, Melania del Cisne (2010)
The marketing system proposes a new concept defined as: advice on brand and image, resulting in a greater chance of a saturated domestic market and exploited but shoddy clothes, display products to the market as quality casual clothes with low costs and stewardship of image capture to customers tired of low quality clothing.